PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN IPA KELAS VII SMP PADA MATERI POKOK INTERAKSI MAKHLUK HIDUP DAN LINGKUNGAN - Ferlita Evelyn Wahyu Septiana evelyn Septiana; Wan Syafi’i syafi'i; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this reserch is to design, development and produce comic as media learning for science in 7th Grade Junior High School. This research was conducted at Department of Biology Education University of Riau, from April until Juni 2015. The type of this reserch is development research using Research and Development (R & D) approach with model ADDIE. The comic have subject Interaction of Living Organisms and The Environment. Make validation test for the media comic that filled by 5 validators. And then, limited trial conducted at 10 student in 7th Grade Junior High School 1 Pekanbaru. The limited trial was used student questionnaire responses. The value of media comis validation can be seen at 5 aspect, there are simplicity, suppression, balance, integration and comic design. The result is media comic can aplication in learning activities in the class. Key Word : Comic, Media Learning for Science, Interaction of Living Organisms and The Environment